205k views
0 votes
You can helps me?
f(x) = x + 1
g(x) = x - 1
(f o g)(x) = ?


User Meim
by
5.8k points

2 Answers

7 votes

♪Answer :

  • f(x) = x + 1
  • g(x) = x - 1

»(f o g)(x)

»f(g(x))

»f(x - 1)

»x - 1 + 1

»x

User MicE
by
5.9k points
2 votes

Answer:

fg(x) = x

Given items:

  • f(x) = x + 1
  • g(x) = x - 1

solve for fg(x):

→ f g(x)

→ f(x - 1)

→ (x - 1) + 1

→ x

note: go form right to left in such function problems.

User David Stevens
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.